Plant cover and species compositions on subarctic green roofs - Lönnqvist, Joel; Blecken, Godecke-Tobias; Viklander, Maria (Luleå tekniska universitet, Arkitektur och vatten, 2017)
Thisstudy looked at the plant cover and species composition of green roofs in a subarctic climate. The study’s aim was to evaluate the cover of plants and moss on green roofs in northern Sweden. Data was gathered from a field survey in summer 2016 andevaluatedroof sections located on buildings in three different towns located on a latitudinal gradient.Apart from plant cover substrate depth, slope andexposure was recorded. The results showed that the average vascular plant cover was low in the two northern locations (32% and 27%) while in the southernmost location it was high (>85%).